Persepsi Generasi Muda Terhadap Profesi Pengrajin Batik Tulis di Purbalingga - Suliyanto Suliyanto; Weni Novandari; Sri Murni Setyawati (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2015)
The aims of this study were to analyze the perception of young generationto theprofession of batik craftsmen and to analyze the reasons of young generation are reluctant to become batik craftsmen in Purbalingga. The study was conducted in Purbalingga with the younger generation who located in centers of painting batik. The data was collected using in-depth interviews, Focus group discussion (FGD), and questionnaires. The data were analyzed using descriptive statistics and nonparametric statistic analysis of binomial test and Cochran test. Based on the result, it can be concluded that perception of young generation to batik craftmen profession as a job are low income job, requires the soul of art, requires persistence, can be done as a side job, no clear career path, providing the freedom of expression, more flexible compared to other jobs, less prestigious, does not require large capital and income uncertainty. The young generations are not willing to become batik craftsmen because of uncertain income, do not have the taste of art, and do not have enough capital.